Penerapan Teknik Akupressure Pada Keluarga Dengan Gout Arthritis - Asiah, Rohani; Turochman, Hidayat (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2023)
Background. According to WHO in 2020, Gouty Arthritis sufferers increased by 11% from the 6.9 billion population in the world, while according to Basic Health Research (2018) East Jakarta reached 6.72%. Gout Arthritis treatment is divided into two, namely pharmacological and nonpharmacological. Non-pharmacological treatment is carried out with herbal and complementary therapies. The acupressure technique is carried out by applying physical pressure to several points on the surface of the body where energy circulates and balances pain symptoms. The purpose of writing is to gain real experience in providing acupressure techniques to families with Gout Arthritis. The research method used is descriptive method and literature study. The descriptive method is a case study approach by taking one family case and applying acupressure technique intervention and providing nursing care. Research Results: After applying the acupressure technique for 3 days, once a day for 15 minutes - 30 minutes, Mrs. I especially Mrs. I with Gout Arthritis experienced a decrease, initially 8.4 mg/dl fell to 6.4 mg/dl. Conclusion The application of acupressure techniques in families with Gout Arthritis was carried out well, namely that the family's knowledge about Gout Arthritis increased and uric acid levels decreased from 8.4 mg/dl to 6.4 mg/dl and the family was able to care for members who experienced Gout Arthritis.